2017
DOI: 10.1111/aos.13377
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between pro‐apoptotic and pro‐survival factors in human retinal pericytes in diabetic‐like conditions

Abstract: Purpose Loss of pericytes is one the key events in the pathogenesis of diabetic retinopathy. We have previously demonstrated that human retinal pericytes (HRP) are more vulnerable to intermittent than stable high glucose concentrations, with an increase in apoptosis. Our aim was to explore the expression of molecules involved in pro‐apoptotic and survival pathways in pericytes cultured in stable/intermittent high glucose and/or hypoxia, to clarify the mechanisms of action of these diabetic‐like stressing stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…22 Further, activation of pro-apoptotic pathways, angiopoietin-2 signaling, and consecutive vasoregression evidenced by pericyte loss have been identified as early pathologic features of diabetic posterior segment complications and blood-retinal barrier breakdown. [23][24][25][26] High HbA1c levels, a sign of poor glycemic control, correlated with systemic and intravitreal levels of VEGF-A. 6,27,28 Moreover, high levels of VEGF in the aqueous humor were to be a risk factor for macular edema after cataract surgery on diabetic patients with nonproliferative retinopathy.…”
Section: Discussionmentioning
confidence: 98%
“…22 Further, activation of pro-apoptotic pathways, angiopoietin-2 signaling, and consecutive vasoregression evidenced by pericyte loss have been identified as early pathologic features of diabetic posterior segment complications and blood-retinal barrier breakdown. [23][24][25][26] High HbA1c levels, a sign of poor glycemic control, correlated with systemic and intravitreal levels of VEGF-A. 6,27,28 Moreover, high levels of VEGF in the aqueous humor were to be a risk factor for macular edema after cataract surgery on diabetic patients with nonproliferative retinopathy.…”
Section: Discussionmentioning
confidence: 98%
“…Glycemic oscillations postprandial (after mealtime) and during fasting might activate oxidative stress, systemic proinflammatory, and proapoptotic signaling pathways and promote microvascular endothelial dysfunction and pericyte dropout. 17,18 Patients with type 1 diabetes have a higher glycemic variability than patients with type 2 diabetes, regardless of overall glycemic control. 19 Given that glucose fluctuation might differ between insulin-dependent and non-dependent diabetic patients, and glycemic variability might promote inflammation and vascular complications, patients with type 1 or type 2 diabetes with insulin dependence seem to be at greater risk for pseudophakic CME.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that HG-induced apoptosis in HRPs involved ERK-Sp1 signaling and ROS. The loss of retinal cells, including retinal pericytes, in individuals with hyperglycemia is important for the pathogenesis of visual system changes in DR. 9 , 22 According to previous studies, HG increases the intracellular nitric oxide and superoxide levels, resulting in endothelial cell and mitochondrial dysfunction, which eventually leads to apoptosis. 22 , 23 , 24 Some mechanistic studies have shown that antiapoptotic effect of retinal pericytes is mediated via the inhibition of nicotinamide adenine dinucleotide phosphate oxidase activation, glyceraldehyde 3-phosphate dehydrogenase activity, and ROS generation.…”
Section: Discussionmentioning
confidence: 93%
“… 2 According to several reports, exposure of pericytes to high glucose (HG) levels reduced their proliferation and induced apoptosis. 2 , 6 , 7 , 8 , 9 Hyperglycemia is known to increase the generation of reactive oxygen species (ROS), especially in retinal vessels. 10 , 11 , 12 , 13 Accordingly, diabetes-related dysfunction of the retinal vasculature may be ameliorated by blocking the generation of ROS.…”
Section: Introductionmentioning
confidence: 99%